Comparative accuracy of ferritin, transferrin saturation and soluble transferrin receptor for the diagnosis of iron deficiency in inflammatory bowel disease. Issue 11 (22nd April 2020) - Daude, Sébastien; Remen, Thomas; Chateau, Thomas; Danese, Silvio; Gastin, Isabelle; Baumann, Cédric; Gueant, Jean Louis; Peyrin‐Biroulet, Laurent
Summary: Background: The diagnosis of iron deficiency is based on ferritin and transferrin saturation (TfS) in inflammatory bowel disease (IBD) patients, yet guideline thresholds are not evidence‐based. Soluble transferrin receptor (sTfR) is one of the best noninvasive tests in patients with inflammation. Aims: To evaluate the accuracy of ferritin and/or TfS for diagnosing iron deficiency in IBD and identify the optimal thresholds of these parameters using sTfR as reference. Methods: Two hundred and two patients (2072 samples) receiving at least one infusion of biologic (vedolizumab or infliximab) were included. Results: In ulcerative colitis patients with C‐reactive protein (CRP) <10 mg/L, optimal iron deficiency diagnostic performances were observed with ferritin and TfS thresholds of 65 µg/L (sensitivity of 0.78 and specificity of 0.76) and 16% (sensitivity of 0.79 and specificity of 0.90), respectively. For ulcerative colitis patients with CRP > 10 mg/L, the thresholds with the best diagnostic performance were 80 µg/L (sensitivity of 0.75 and a specificity of 0.82) for ferritin and 11% for TfS (sensitivity of 0.75 and a specificity of 0.82). There was no added value for combined ferritin and TfS. No ferritin or TfS threshold had good diagnostic performance in Crohn's disease patients (AUC for ferritin was 0.65 (95% CI 0.55‐0.75) and the AUC for TfS was 0.70 (95% CI 0.61‐0.78). Conclusion: Ferritin and TfS are reliable parameters for iron deficiency diagnosis only in ulcerative colitis patients, at thresholds different from current guidelines. In Crohn's disease patients, sTfR should be used given the poor diagnostic performance of ferritin and TfS.